Repurposing the past: Sarnies as the economic power of heritage in Bangkok - Mya Myint Thu (The Journal of City: Branding and Authenticity, 2025)
Background: The adaptive reuse of heritage buildings has emerged as a sustainable strategy for urban development, harmonizing historical preservation with modern functionality. This paper examines the transformation of Sarnies Bangkok, a 150-year-old former boat repair shop, into a thriving café, and its role as a driver of urban regeneration in Bangkok’s historic Old Town. Situated near the Chao Phraya River and Charoen Krung Road, the site leverages its rich historical and cultural significance to enhance urban identity, foster community engagement, and stimulate local economic growth. Methods: Using a qualitative research framework, the study employs architectural analysis and a review of relevant conservation practices to assess the socio-economic and cultural impacts of the project. Findings: The findings reveal that Sarnies Bangkok not only preserves the site’s architectural and historical integrity but also catalyzes heritage tourism, creates local employment opportunities, and strengthens the community’s cultural connection to the space. By employing sustainable design practices, the project mitigates environmental impact while maximizing cultural and economic benefits. Conclusion: This study concludes that adaptive reuse, as exemplified by Sarnies Bangkok, represents a replicable model for sustainable urban renewal. By integrating inclusive strategies, such projects can balance the risk of gentrification with the need for economic revitalization and cultural preservation, offering valuable insights for future urban development initiatives in rapidly modernizing cities. Novelty/Originality of this article: This article introduces a novel approach to adaptive reuse by highlighting the integration of minimal intervention, sustainability, and community engagement in the transformation of Sarnies Bangkok, a 150-year-old boat repair shop, into a thriving café. By contextualizing the project within Bangkok’s socio-economic and urban evolution, it provides a replicable framework for balancing heritage preservation with modern urban demands, offering fresh insights for sustainable urban regeneration.